(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Spinal cord tumors are one of the pressing problems of neurosurgery. Spinal cord tumors account for 2% of all neoplasms and 3% of nervous system pathologies in adults[V.V. Stupak, S.V. Shabanov, I.V. Pendyurin, S.S. RabinovichResults of surgical treatment of patients with extramedullary hourglass tumors]. Most often, spinal cord tumors are observed in a socially active group of people aged 30–50 years, which determines the great relevance of this problem[V.V. Stupak, S.V. Shabanov, I.V. Pendyurin, S.S. RabinovichResults of surgical treatment of patients with extramedullary hourglass tumors]. According to the types of tumor incidence]. Spinal tumors account for 5–10% of all central nervous system tumors.